KNOWLEDGE AND ATTITUDE OF PARENTS, TEACHERS AND STUDENTS TOWARDS THE INTEGRATION OF HIV POSITIVE ADOLESCENTS IN REGULAR CLASSES IN OKE-OGUN, OYO STATE, NIGERIA. - FEHINTOLA, J. OLUSOLA (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
HIVIAIDS isa global problem. The devastating effect of HIVIAIDS on the world’s population, particularly people in Sub-Saharan Africa (SSA) cannot be overemphasised Unfortunately, the realisation of this came relatively recent to Nigeria, the continents’ most populous nation. For along while, many Nigerians viewed AIDS as a figment of imagination of some scientists and foreign, not relevance to the black man. Asa result, Nigeria has become one of the most affected countries in the world. This study investigated the attitude of teachers, students and parents towards integration of HIV positive adolescents in regular classes in Oke-Ogun, Oyo state. Two hundred and eighty-six participants were covered in this study. Participants were drawn from 42 schools in urban, semi-urban and rural areas in each local government of Oke-Ogun. They include 54 teachers, 118 students and 114 parents. Data were generated through two specifically designed instruments which tested knowledge and attitude towards integrating HIV positive adolescents in regular classes and knowledge of HIV/AIDS. The measurement scale for this study was a four point Likert-type scale (Strongly Agree, Agree, Disagree, and Strongly Disagree). The instrument contained 18 and 17items for the teachers and parents respectively each testing attitude while the second instrument was a 15-item knowledge test, the same for all these participants. Two hypotheses were tested at a = 0.05 level of significance. The data were analysed using ANOVA. The finding revealed that in all three sub-samples, groups with higher level of education had more positive attitude towards integration of adolescents with HlV/AIDS into regular schools as well as higher knowledge score. Generally, parents showed less favourable attitudes when compared to teachers and students and this may be a possible obstacle to the integration of HIV positive adolescents into regular schools. There is obviously a need for a coordinated public intervention aimed at informing ’the public about HIV/AIDS. Suggestion and recommendation were provided to assist the educational sector; policymakers and other stakeholders involved in the fight against HIV/AIDS.